On the Indexes in Some Continental Editions of Milton's Pro Populo Anglicano Defensio and Salmasius's Defensio Regia, with an Addendum on the Publisher Adrienne Brillet. - Vozar, T M (Library, 2024)
This article examines the indexes in some Continental editions of John Milton's Pro populo Anglicano defensio and Claudius Salmasius's Defensio Regia. Previously little noticed, the indexes are treated here both as a marketing device for publishers and as a guide for the perusal of the polemics. The authorship of the index to the Pro populo Anglicano defensio is considered in relation to the bibliography of that work as well as Milton's attitudes toward indexing. The Miltonic index is shown to possess a rhetorical construction in its own right and to provide a means for readers to easily access the main points of the controversy. The later Salmasian index is approached similarly. An addendum highlights the career of the Parisian publisher Adrienne Brillet, who printed both indexes in a unique joint edition of the polemics, with special attention to her dealings with Salmasius.